2022
DOI: 10.1371/journal.pone.0265073
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth versus face-to-face visits: A comprehensive outpatient perspective-based cohort study of patients with kidney disease

Abstract: Background Telenephrology has become an important health care delivery modality during the COVID-19 pandemic. However, little is known about patient perspectives on the quality of care provided via telenephrology compared to face-to-face visits. We aimed to use objective data to study patients’ perspectives on outpatient nephrology care received via telenephrology (phone and video) versus face-to-face visits. Methods We retrospectively studied adults who received care in the outpatient Nephrology & Hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Telehealth also allows health care providers to reach patients and other specialists remotely, allows them to reach larger segments of the population, alleviates workforce shortages in remote areas, and improves care coordination [1][2][3][4][5][6]. Patient satisfaction with telehealth has been well documented, particularly among residents from rural communities [2,4,[6][7][8], with as many as 95% of patients rating telehealth visits as "better than" or "just as good" as face-to-face visits [6,9,10]. Specifically, studies of oncology patients have reported high levels of satisfaction with telehealth [3][4][5]8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Telehealth also allows health care providers to reach patients and other specialists remotely, allows them to reach larger segments of the population, alleviates workforce shortages in remote areas, and improves care coordination [1][2][3][4][5][6]. Patient satisfaction with telehealth has been well documented, particularly among residents from rural communities [2,4,[6][7][8], with as many as 95% of patients rating telehealth visits as "better than" or "just as good" as face-to-face visits [6,9,10]. Specifically, studies of oncology patients have reported high levels of satisfaction with telehealth [3][4][5]8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Majority aged 50–64 years old Feedback questionnaire Remote consultation 88% of patients replied positively about their experience. Significant impact on the overall time saved, as well as convenient [40%] Androga et al [ 16 ] Nephrology Clinic in USA 3361 CKD outpatients (stages 1–5, treatment unspecified) Aged 47–75 years old, predominantly White Patient Satisfaction Survey Not validated Consultation over telephone/ video call There was no difference in patient survey responses for the above when telehealth was compared to face-to-face visits [80%] Antoun et al [ 20 ] HHD and ICHD in UK 20 adult CKD patients (10 ICHD, 10 HHD) 70% male, Aged 52–77 years old Semi-structured telephone interviews Not validated QoL, Wellbeing and PA QoL, Wellbeing, PA and Medical care all impacted ICHD negatively. HHD little change Focus on impact of shielding.…”
Section: Resultsmentioning
confidence: 99%
“…One study found significant differences in preferences according to the age of the patient, with older patients opting for face-to-face appointments. There were no differences in relation to ethnicity and gender [ 16 ]. A recurring issue with telemedicine was the inability to have physical issues examined by the consulting clinician [ 15 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, patients may prefer the potential convenience of telehealth visits; on the other hand, patients may be discontented by new barriers related to technology usage or unmet expectations of what can and should be achieved during a medical encounter (e.g., physical examination). Prior studies have suggested that patient satisfaction for telehealth visits may be on par with or better than in‐person visits 5–10 . However, whether this is true in a safety‐net, adult primary care population is not well‐established.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have suggested that patient satisfaction for telehealth visits may be on par with or better than in‐person visits. 5 , 6 , 7 , 8 , 9 , 10 However, whether this is true in a safety‐net, adult primary care population is not well‐established. Additionally, differences in satisfaction between audio‐only and video visits are not well‐described.…”
Section: Introductionmentioning
confidence: 99%